A new variant (c.1A>G) in LDLRAP1 causing autosomal recessive hypercholesterolemia: Characterization of the defect and response to PCSK9 inhibition - Rodríguez-Jiménez, Carmen; Gómez-Coronado, Diego; Frías Vargas, Manuel; Cerrato, Francisca; Lahoz, Carlos; Saban-Ruiz, Jose; González-Nieto, Daniel; Lasunción, Miguel A.; Mostaza, José M.; Rodríguez-Nóvoa, Sonia (Atherosclerosis, 2019)
Autosomal recessive hypercholesterolemia (ARH) is a rare disorder caused by mutations in LDLRAP1, which impairs internalization of hepatic LDL receptor (LDLR). ARH patients respond relatively well to statins or the combination of statins and Ezetimibe, but scarce and variable data on treatment with PCSK9 inhibitors is available. We aimed to identify and characterize the defect in a hypercholesterolemic patient with premature cardiovascular disease and determine the response to lipid-lowering treatment. Gene sequencing revealed a homozygous c.1A > G:p.? variant in LDLRAP1. Primary lymphocytes were isolated from the ARH patient, one control and two LDLR-defective subjects, one LDLR:p.(Cys352Ser) heterozygote and one LDLR:p.(Asn825Lys) homozygote. The patient had undetectable full-length ARH protein by Western blotting, but expressed a lower-than-normal molecular weight peptide. LDLR activity was measured by flow cytometry, which showed that LDL binding and uptake were reduced in lymphocytes from the ARH patient as compared to control lymphocytes, but were slightly higher than in those from the LDLR:p.(Cys352Ser) heterozygote. Despite the analogous internalization defect predicted in ARH and homozygous LDLR:p.(Asn825Lys) lymphocytes, LDL uptake was higher in the former than in the latter. LDL-cholesterol levels were markedly reduced by the successive therapy with Atorvastatin and Atorvastatin plus Ezetimibe, and the addition of Evolocumab biweekly decreased LDL-cholesterol by a further 39%. The LDLRAP1:c.1A > G variant is associated with the appearance of an N-terminal truncated ARH protein and to reduced, although still significant, LDLR activity in lymphocytes. Residual LDLR activity may be relevant for the substantial response of the patient to Evolocumab. [Display omitted] •A new variant c.1A > G in LDLRAP1 causing autosomal recessive hypercholesterolemia was found.•c.1A > G in LDLRAP1 produces an N-terminal truncated autosomal recessive hypercholesterolemia (ARH) protein.•Lymphocyte LDLR activity is significantly reduced but far from abolished.•Evolocumab biweekly substantially lowered LDLc levels in ARH patients.